Oral supplement enriched in HMB combined with pulmonary rehabilitation improves body composition and health related quality of life in patients with bronchiectasis (Prospective, Randomised Study). Issue 5 (October 2016) - Olveira, Gabriel; Olveira, Casilda; Doña, Esperanza; Palenque, Francisco Javier; Porras, Nuria; Dorado, Antonio; Godoy, Ana M.; Rubio-Martínez, Elehazara; Rojo-Martínez, Gemma; Martín-Valero, Rocío
Summary: Background & aims: Pulmonary Rehabilitation (PR) is recommended for bronchiectasis but there is no data about its effect on body composition. The aim of this study is to assess the effect of Pulmonary Rehabilitation (PR) for 12 weeks in normally-nourished non-cystic-fibrosis bronchiectasis patients compared with the effect of PR plus a hyperproteic oral nutritional supplement enriched with beta-hydroxy-beta-methylbutyrate (HMB) on body composition, muscle strength, quality of life and serum biomarkers. Methods: single center randomized controlled trial, parallel treatment design: Participants were randomly assigned to receive PR for 12 weeks or PR plus ONS (PRONS) (one can per day). Outcome assessments were performed at baseline, 12 weeks and 24 weeks: body composition (Dual-energy X-Ray Absorptiometry (DEXA), mid-arm muscle circumference (MAMC), phase angle by Bio-impedance), health related quality of life (Spanish QOL-B-V3.0, Physical Functioning Scale), handgrip strength, diet questionnaire, and plasma levels of prealbumin, myostatin and somatomedin-c. Results: Thirty patients were randomized (15 per group) without differences in clinical and respiratory variables. In the PRONS group bone mineral density (BMD), mean and maximum handgrip dynamometry, MAMC, QOLB and prealbumin were significantly increased from baseline at 12 and 24 weeks and Fat free Mass (FFM) and FFM index, at 12 weeks. In the PR group only mean handgrip dynamometry and prealbumin were significantly increased at 12 and 24 weeks. In both groups plasma myostatin was reduced at 12 weeks (without significant differences). Conclusion: The addition of a hyperproteic ONS enriched with HMB to Pulmonary Rehabilitation could improve body composition, BMD, muscle strength and health related quality of life in bronchiectasis patients. Clinical Trials NumberNCT02048397 .